1989
DOI: 10.1111/j.1476-5381.1989.tb12659.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the adrenomedullary dependence of κ‐opioid agonist‐induced diuresis in conscious rats

Abstract: 1 The dependence of K-opioid agonist-induced diuresis, upon an intact and functional adrenal medulla in conscious rats, was investigated in order to test the hypothesis that the diuresis is mediated by a blood-borne 'diuretic factor', of adrenomedullary origin, released by K-opioid receptor stimulation. 2 Confirming previous observations, adrenal demedullation significantly attenuated diuretic responses to the K-opioid agonists U50488H, ethylketocyclazocine (EKC) and tifluadom, but did not affect basal urine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Some of this effect is likely mediated via inhibition of vasopressin release (Floyd et al, 2009). However, bilateral adrenal demedullation significantly attenuates the diuretic response to KOR agonists (Ashton et al, 1989;Blackburn et al, 1986;Borkowski, 1989), raising the possibility that kappa agonists act, at least in part, on cells in the adrenal medulla. Autoradiography binding assays (Quirion et al, 1983) as well as RT-PCR and Northern analysis (Wittert et al, 1996) suggest KOR expression in the kidney and adrenal gland.…”
Section: Resultsmentioning
confidence: 99%
“…Some of this effect is likely mediated via inhibition of vasopressin release (Floyd et al, 2009). However, bilateral adrenal demedullation significantly attenuates the diuretic response to KOR agonists (Ashton et al, 1989;Blackburn et al, 1986;Borkowski, 1989), raising the possibility that kappa agonists act, at least in part, on cells in the adrenal medulla. Autoradiography binding assays (Quirion et al, 1983) as well as RT-PCR and Northern analysis (Wittert et al, 1996) suggest KOR expression in the kidney and adrenal gland.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the demonstration of kappa opioid binding sites in the kidney (Quirion et al, 1983;Slizgi & Ludens, 1985), it has been suggested that kappa agonists have a direct renal action. At the same time it has been shown in rats that bilateral adrenal demedullation significantly attenuated the diuretic responses to the kappa-opioid agonists U-50488H, ethylketocyclazocine and tifluadom, but did not affect basal urine output, frusemide-induced diuresis or the antidiuretic response to morphine and buprenorphine (Ashton et al, 1989;Blackburn et al, 1986;Borkowski, 1989) indicating a link between the adrenal medulla and kappa-opioid induced diuresis and suggesting that a peripheral mechanism may also be involved in mediating this effect.…”
Section: Discussionmentioning
confidence: 94%
“…As adrenaline originates exclusively from the adrenal medulla, plasma levels provide an estimate of adrenal medullary activity [34]. It can therefore be inferred that U-62066E at the dose we used does not influence adrenal medullary activity although studies have shown that the adrenal medulla has a role in the diuretic actions of tcreceptor agonists [35,36].…”
Section: Discussionmentioning
confidence: 99%